1963
DOI: 10.1136/bmj.1.5337.1064
|View full text |Cite
|
Sign up to set email alerts
|

Myelopathy in Hepatic Cirrhosis

Abstract: Transient neurological changes occurring in patients suffering from hepatic precoma and coma are well known (Adams and Foley, 1953;Summerskill et al., 1956). The development of permanent neurological deficits in such patients has only recently been appreciated. It is becoming increasingly clear that permanent neurological changes referable to many systems are not uncommon in these patients. During the past five years R. D. Adams and M. Victor (personal communication, 1962) Investigations revealed normal uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1964
1964
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The first documentation of hepatic myelopathy from the Indian subcontinent was provided by Pant et al 4. There is a paucity of literature of hepatic myelopathy causing quadriparesis, that is, mainly affecting cervical cord.…”
Section: Discussionmentioning
confidence: 99%
“…The first documentation of hepatic myelopathy from the Indian subcontinent was provided by Pant et al 4. There is a paucity of literature of hepatic myelopathy causing quadriparesis, that is, mainly affecting cervical cord.…”
Section: Discussionmentioning
confidence: 99%
“…Autopsy studies in patients with HM have shown selective demyelination in the corticospinal tracts, Betz cell loss and some authors have even regarded HM as a restricted form of encephalopathy. [10] Nitrogenous toxins, e.g., ammonia that inappropriately enters the systemic circulation as a result of shunting, are implicated in its pathogenesis. [10] HM responds poorly to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Nitrogenous toxins, e.g., ammonia that inappropriately enters the systemic circulation as a result of shunting, are implicated in its pathogenesis. [10] HM responds poorly to treatment. Liver transplantation may reverse some of the neurological changes.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] In India, HM was reported for the first time by Pant et al, who described two cases of spastic paraparesis in patients with liver cirrhosis, one with a spontaneous portocaval shunt and the other with a surgical portocaval anastomosis. [5] The typical clinical presentation of this disorder is of a patient with underlying chronic liver disease, developing progressive pure motor spastic paraparesis with the minimal or no sensory deficit and without bowel and bladder involvement. Most patients report prior episodes of hepatic encephalopathy and in many cases, the development of myelopathy follows the creation of surgical shunts.…”
Section: Introductionmentioning
confidence: 99%